Elements of Eating Morality According to Bediuzzaman Said Nursi’s Views: A Complementary to The Basic Concept of Food in Islam - Siti Jamilah Mohd; Nurrulhidayah Ahmad Fadzillah (USIM Press, 2024)
Vol. 23 No. 1 (2020): Journal of Islamic Social Sciences and Humanities